Transactions on edutainment X - Müller, Wolfgang; Iurgel, Ido; Petta, Paolo; Urban, Bodo; Cheok, Adrian David; Pan, Zhigeng (Lecture Notes in Computer Science, 2013)
This journal subline serves as a forum for stimulating and disseminating innovative research ideas, theories, emerging technologies, empirical investigations, state-of-the-art methods, and tools in all different genres of edutainment, such as game-based learning and serious games, interactive storytelling, virtual learning environments, VR-based education, and related fields. It covers aspects from educational and game theories, human-computer interaction, computer graphics, artificial intelligence, and systems design. This special issue consists of two parts: the first one features original research papers on interactive digital storytelling in the applied context of edutainment; the second part contains a selection of revised and expanded best papers from the 4th eLearning Baltics (eLBa 2011) conference. The papers on digital storytelling have been split into sections on theory, technology, and case studies; the eLBA 2011 conference papers deal with technology and applications, case studies and mobile applications, and game-based learning and social media.